PENGARUH GAYA KEPEMIMPINAN DAN FASILITAS KERJA TERHADAP KINERJA PEGAWAI DEALER GALAXY MOTOR KEDIRI - Erlin Viyona Widianti; Anwar Bowo Leksono; Udik Jatmiko (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
The problems rased in this research are leadership styles and work facilities that still need to be considered to support employee performance. The purpose of this study was to determine the significance of the influence between leadership style and work facilities both partially and simultaneously. The population in this study numbered 49, 1 of wich was the head of the branch and as a sample were all employees who were still active as many as 48 active employees. The analytical method used is quantitative with differential statistics including validity, reliability, classic assumtions, multiple linear regression and hypothesis testing. Based on the results of the study, it was found that the regression equation Y= 11,540+1,296X1+ 0,812X2. Based on the partial test it was found that the significant value was t (0,000) <0,05, meaning that partially there is a positive and significant influence between leadership style on employee performance. Significant value of t (0,006) < 0,05, wich means that partially there is positive and significant influence between work facilities on employee performance ar Galaxy Motor Kediri Dealers. Simultaneously leadership style and work facilities have on effect on employee performance as a evidance by the value of F 21,752 > 3,204 and a significant F of 0,000<0,05